2018
DOI: 10.1016/j.eurpsy.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the relationship between mental health, radicalization and mass violence

Abstract: Radicalization is a process, by which individuals adopt extreme political, social and religious ideation that leads to mass violence acts. It has been hypothesized that mental health characteristics might be associated with a risk of radicalization. However, a qualitative synthesis of studies investigating the relationship between mental health and radicalization has not been performed so far. Therefore, we aimed to perform a systematic review of studies examining the association between mental health characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 70 publications
1
58
0
2
Order By: Relevance
“…In this paper, social adversity is defined specifically in terms of perceived discrimination and exposure to violence, which represent two crucial risk factors for violent radicalization [7, 8]. The available empirical evidence shows that different forms of discrimination are related with an increased support for radical actions [4, 9, 10] and an increase in terrorist attacks [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, social adversity is defined specifically in terms of perceived discrimination and exposure to violence, which represent two crucial risk factors for violent radicalization [7, 8]. The available empirical evidence shows that different forms of discrimination are related with an increased support for radical actions [4, 9, 10] and an increase in terrorist attacks [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a paucity of studies investigating how discrimination and exposure to violence are linked to Sympathy for Violent Radicalization (SVR) in both majority and minority groups in the general population. Given the growing number of homegrown young men who embrace violent radicalization processes, as well as the present growth in the number of terrorist attacks, hate crimes and xenophobic incidents worldwide [14–16], the study of the social determinants of SVR represents a top priority in a public health perspective [7, 17]. Of importance, evidence on potential risks and protective factors able to buffer the negative consequences of social adversity on risk of SVR is warranted to inform prevention and intervention actions.…”
Section: Introductionmentioning
confidence: 99%
“…Figuring out those who are vulnerable to depression and who need professional advice during a protest is a practical concern for clinical psychologists. While the relationship between depression and extremism and terrorist actions is still debatable [41], this research found that depression and support for radical actions as political attitude are associated. Follow-up research is necessary to further examine those who are more likely to conduct deviant and radical activities due to feelings of depression.…”
Section: Discussionmentioning
confidence: 70%
“…Depression is a mix of negative feelings including sadness, self-disappointment, inefficacy, guilt, etc. Regarding the relationship between depression and radicalism, there was research that investigated how depression as a mental illness related to extreme behaviour and terrorist attacks [41]. However, the relationship between depression and support for radical actions as a general political attitude is rarely discussed.…”
Section: Hypothesis 3d (H3d) Fomo Relates Positively To Perceived Somentioning
confidence: 99%
“…The Lexico Dictionary Online defines radicalization as "the process of causing someone to adopt radical positions on political or social issues" [1]. Radicalization has also been defined as a behavior by which individuals embrace a political, social, or religious ideology that leads to terrorist acts [2]. Prevent (the British agency for the prevention of radicalization) defines radicalization as the practice leading people to endorse terrorism or radical ideologies leading to terrorism [3].…”
Section: Introductionmentioning
confidence: 99%